2011
DOI: 10.3126/hjs.v6i8.2699
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of RAPD-PCR conditions for the study of genetic diversity in Nepal’s <i>Swertia chirayita</i> (Roxb. Ex Fleming) H. Karst

Abstract: Of the 30 species (including five varieties) of the genus Swertia in Nepal, nine have been reported to possess medicinal properties. Among these, S. chirayita is the most valuable species, with high demand in domestic and international markets. Nepal's S. chirayita and related species are being recklessly exploited for commercial purposes. Two problems that have emerged with this lucrative market are (a) adulteration and fraudulent labeling of S. chirayita, and (b) depletion of S. chirayita and allied species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…For the assessment of genetic diversity, a variety of (PCR)-based molecular marker techniques are now available. Rand Amplified Polymorphism DNA (RAPD), Inter-Simple Sequence Repeats (ISSR) and Simple Sequence Repeats (SSR) markers are the most widely used molecular markers in diversity testing (Shrestha et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…For the assessment of genetic diversity, a variety of (PCR)-based molecular marker techniques are now available. Rand Amplified Polymorphism DNA (RAPD), Inter-Simple Sequence Repeats (ISSR) and Simple Sequence Repeats (SSR) markers are the most widely used molecular markers in diversity testing (Shrestha et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…The result indicated that ITS fragment can be used in identification as a barcoding marker for Swertia. The optimization of the RAPD-PCR conditions (Shrestha et al, 2011) and genetic diversity of 34 accessions of S. chirayita including six outlier species were assessed in Nepal (Shrestha et al, 2013). Of the total 285 amplified bands scored for S. chirayita, 263 (92.8%) were polymorphic.…”
Section: Introductionmentioning
confidence: 99%